The Effect of Noise Pollution on Blood Pressure and Heart Rate of Beauty Salon Workers - Rawa Kamaran Fattah; Abdulrahman K. Suliman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study demonstrates the effect of noise on the cardiovascular system of the beauty salon workers, and to find solutions to reduce the noise in beauty salons. The measured parameters in this research are the blood pressure and heart rate at standing, rest, after 2 min, after 4 min, and after 6 min, and the intensity of the hair drier measured. The devices used in this research are the digital sphygmomanometer utilized to measure the blood pressure, and heart rate of workers, the sound meter used to measure the sound intensity of the hair dryer, and the noise level. According to the findings, 70% of workers have elevated heart rates, 70% have raised systolic blood pressure, 65% have increased diastolic blood pressure, and 65% have disturbed sleeping patterns.